Optical and Photoelectric Properties of Nanolamellar Structures Obtained by Thermal Annealing of InSe Plates in Zn Vapours. Issue 4 (15th January 2018) - Untila, Dumitru; Evtodiev, Igor; Caraman, Iuliana; Spalatu, Nicolae; Dmitroglo, Liliana; Caraman, Mihail
Abstract : The structural, optical and photoelectric properties of InSe crystals grown by Bridgman–Stockbarger method and ZnSe/InSe structures obtained on InSe by thermal annealing in Zn vapours are studied in this paper. The study of structural properties confirms that ZnSe compound is formed. The analysis of photoelectric properties reveal that both the ZnSe‐InSe composite layer and the composite/InSe heterojunction are photosensitive in the VIS‐NIR spectral region. Abstract : A III B VI semiconductors, and InSe in particular, are perspective materials for application in electronic and optoelectronic devices. The results of structural, optical and photoelectric properties analysis of InSe crystals grown by Bridgman–Stockbarger method and thermally annealed in Zn vapours are presented. The analysis revealed the ZnSe compound formation onto surface of InSe plates. The ZnSe‐InSe composite layer and the composite/InSe heterojunction are photosensitive and photoluminescent in the VIS‐NIR spectral region.